2002
DOI: 10.1038/sj/mp/4000974
|View full text |Cite
|
Sign up to set email alerts
|

Role of bombesin (BN)-like peptides/receptors in emotional behavior by comparison of three strains of BN-like peptide receptor knockout mice

Abstract: Keywords: gastrin-releasing peptide receptor (GRP-R); bombesin receptor subtype-3 (BRS-3); neuromedin B receptor (NMB-R); light-dark (L-D) box test; elevated plus maze test; anxiety; emotion; knockout mice Bombesin (BN)-like peptides are involved in the regulation of a wide variety of behaviors, such as spontaneous activity and feeding. We assessed the role of BN-like peptides/receptors in emotional and/or anxietyrelated behavior using three strains of knockout mice, each deficient in a single BN-like peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…A balance between excitatory and inhibitory transmission is critical for many brain functions. Previous reports show that the GRP in the amygdala is inovolved in behavioral fear [18,31-36]. In addition to the amygdala, recent studies show that lesion of the ACC produced an impairment in trace fear conditioning [37] and electrical stimulation of the ACC induced fear memory [38].…”
Section: Discussionmentioning
confidence: 99%
“…A balance between excitatory and inhibitory transmission is critical for many brain functions. Previous reports show that the GRP in the amygdala is inovolved in behavioral fear [18,31-36]. In addition to the amygdala, recent studies show that lesion of the ACC produced an impairment in trace fear conditioning [37] and electrical stimulation of the ACC induced fear memory [38].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the levels of the MCH receptor and prepro-MCH mRNAs in the hypothalamus of BB 3 receptor knockout mice were higher than those of controls, suggesting that up-regulation of the MCH receptor and MCH occurs in the knockout mice, which triggers hyperphagia and probably upsets the mechanism by which leptins decrease MCH receptors and feeding (Maekawa et al, 2004). Studies of BB 3 receptor knockout mice suggest that this receptor is important in various behavioral effects, including the neural mechanisms that regulate social isolation (Yamada et al, 2000a), and are important in modulating emotion including forms of anxiety (Yamada et al, 2002a).…”
Section: Bb 3 Receptor In Diseasesmentioning
confidence: 99%
“…More recent studies demonstrate BRS-3 receptors are present on pancreatic islets [8] and BRS-3 knockout animals have altered plasma insulin levels and altered glucose transporter 4 function [28,30]. Furthermore, from target receptor deletion (knockout) and expression studies, it has been reported that the BRS-3-receptor is frequently over-expressed by various tumors [7,18,34,40], its presence plays a role in tumor invasiveness [13,15,18,57], a role in lung development, bronchial epithelial cell proliferation and lung injury [15,4143,53], a role in taste preference [63], social response/anxiety [61,62], and may play an important role in regulating gastrointestinal motility [32]. …”
Section: Introductionmentioning
confidence: 99%